Impact of Historic Environments on Child's Cultural Identity and Architectural Heritage Awareness: CATCH (Children-Architects to Create Homes), Erasmus plus Project Experience - Ciftci, Aynur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
This paper presents a multi-cultural experience based on architectural heritage that took place between 2014-2016 with 555 primary/secondary school students from six European partner countries: Belgium, Greece, Italy, Poland, Portugal, with Turkey as the coordinator. The project entitled 'C.A.T.C.H' is a European Union Erasmus + Project and consists of 16 activities designed for children around architectural themes as an instrument for creating an awareness of the built environment and cultural values. The six interrelated activities prepared by the author and based on the 'learning by playing' method aimed to inform children about their architectural heritage and the historic environment. The outputs of the multi-cultural project comprised a book, a website, six e-magazines, a Facebook page and a glossary of architectural terms. The impact of the project can be seen through the adaptations of other courses, the establishment of new relations with architecture schools, the participation in national competitions and the permanent/temporary exhibitions of the outputs of the children. The results of this project show clearly that national education programmes need courses based on cultural values and architectural heritage in order to increase children's awareness and to remind them of their role in its conservation while strengthening their cultural identity.
Keywords: Historic environment; children; cultural identity; architectural heritage; awareness; education; Arts & Humanities - Other Topics